Body-as-Subject in the Four-Hand Illusion - Liang, Caleb; Lee, Yen-Tung; Chen, Wen-Yeo; Huang, Hsu-Chia (Frontiers in Psychology, 2018)
In a recent study (Chen et al. 2018), we conducted a series of experiments that induced the “four-hand illusion”: using a head-mounted display (HMD), the participant adopted the experimenter’s first-person perspective (1PP) as if it was his/her own 1PP. The participant saw four hands via the HMD: the experimenter’s two hands from the adopted 1PP and the subject’s own two hands from the adopted third-person perspective (3PP). In the active four-hand condition, the participant tapped his/her index fingers, imitated by the experimenter. Once all four hands acted synchronously and received synchronous tactile stimulations at the same time, many participants felt as if they owned two more hands. In this paper, we argue that there is a philosophical implication of this novel illusion. According to Merleau-Ponty (1945/1962) and Legrand (2010), one can experience one’s own body or body-part either as-object or as-subject but cannot experience it as both simultaneously, i.e. these two experiences are mutually exclusive. Call this view the Experiential Exclusion Thesis. We contend that a key component of the four-hand illusion—the subjective experience of the 1PP-hands that involved both “kinesthetic sense of movement” and “visual sense of movement” (the movement that the participant sees via the HMD)—provides an important counter-example against this thesis. We argue that it is possible for a healthy subject to experience the same body-part both as-subject and as-object simultaneously. Our goal is not to annihilate the distinction between body-as-object and body-as-subject, but to show that it is not as rigid as suggested by the phenomenologists.